A new proof of the characterization of the weighted Hardy inequality - Bernardis, Ana Lucia (2005)
Maz'ja and Sinnamon proved a characterization of the boundedness of the Hardy operator from Lp(v) into Lq(w) in the case 0 < q < p, 1 < p < ∞. We present here a new simple proof of the sufficiency part of that result. © 2005 The Royal Society of Edinburgh.